2018
DOI: 10.1111/jopr.12987
|View full text |Cite
|
Sign up to set email alerts
|

Digital Learning Resources for Prosthodontic Education: The Perspectives of a Long‐Term Dental Educator Regarding 4 Key Factors

Abstract: Technological advances have led to the introduction of 3D education programs specifically designed for dentistry, leading to the author's use of these programs in the education of dental students. Based on this usage, this paper proposes there are 4 key factors that can enhance student education (spatial ability, interactivity, critical thinking, and clinical correlations with integration of multiple dental disciplines). These key factors can be incorporated into student learning through the use of 3D educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Previous studies have shown that virtual 3D models can be used in dental education to enhance student learning 7 and student spatial visualization 8 . Many of the disadvantages of using physical teeth in the classroom can be alleviated by using virtual 3D models of natural teeth.…”
Section: Figurementioning
confidence: 99%
“…Previous studies have shown that virtual 3D models can be used in dental education to enhance student learning 7 and student spatial visualization 8 . Many of the disadvantages of using physical teeth in the classroom can be alleviated by using virtual 3D models of natural teeth.…”
Section: Figurementioning
confidence: 99%
“…These devices could also open up many applications through the use of digitized 3D files [3][4][5][6][7]. They were reported to improve the capacity of medical and dental students of learning disciplines such as anatomy [4,7,8]. Moreover, the development of educational platforms and hybrid teaching is especially useful in these times of COVID-19, as they increase the educational possibilities, that include learning of spatial ability, interactivity, critical thinking and decision-making [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The use of virtual 3D models can be beneficial to student learning in dental education . This is accomplished by engaging spatial visualization, which has been shown to be correlated to improved student performance in the medical field …”
mentioning
confidence: 99%
“…The use of virtual 3D models can be beneficial to student learning in dental education. 1 This is accomplished by engaging spatial visualization, which has been shown to be correlated to improved student performance in the medical field. [2][3][4] In the University of Iowa College of Dentistry preclinical removable partial denture (RPD) course, great emphasis is placed on the design aspect of RPD treatment.…”
mentioning
confidence: 99%